Use of carambola (Averrhoa carambola L. 'Fwang Tung') fruit at two stages of maturity for fresh-cut products - Teixeira, G. H A [UNESP]; Durigan, J. F. [UNESP]; O'Hare, T. J.; Alves, R. E. (My University, 2005)
Carambola fruit ('Fwang Tung') were picked at two stages of maturity: mature-green (50% yellow) and mature (100% yellow). Fruit were washed with water, dipped in NaOCl solution (200 mg.L-1 for 5 minutes), and stored over night at 10°C. Fruit were sliced manually in to pieces of approximately 1 cm thickness. Slices were rinsed with NaOCl solution at 20 mg.L-1, drained for 3 minutes, and packaged in polyethylene tereftalate (PET) trays provided with a fit cover (Neoform® N94). Packages were stored at 6.5°C and 85% RH for 9 days, and samples taken every 3 days for physical, chemical and biochemical analysis, respiration, and internal atmosphere composition. Immediately after cutting, slices at both stages of maturity showed a wounding response with a 5-fold increase in respiration rate. Polygalacturonase (PG) and polyphenol oxidase (PPO) activity did not differ between stages of maturity. Despite the less mature stage being less preferred at the sensory evaluation owing to its greenish peel, the best stage of maturity for carambola fresh-cut production was mature-green, due to a higher resistance to cutting, and presenting a better colour and appearance maintenance for up to 9 days.
Keywords: Browning; Modified atmosphere; Respiration; Sensory evaluation; Wounding response